2010
DOI: 10.1002/jbmr.25
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic increase in cortical thickness induced by femoral marrow ablation followed by a 3-month treatment with PTH in rats

Abstract: We previously reported that following mechanical ablation of the marrow from the midshaft of rat femurs, there is a rapid and abundant but transient growth of bone, and this growth is enhanced and maintained over a 3-week period by the bone anabolic hormone parathyroid hormone (PTH). Here, we asked whether further treatment with PTH or bisphosphonates can extend the halflife of the new bone formed in lieu of marrow. We subjected the left femur of rats to mechanical marrow ablation and treated the animals 5 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…When subjected to x-ray analysis, ablated femurs from rats treated with PBS revealed mildly enhanced radiopacity compared with control rats, similar to previous results in younger animals [2,3]. In contrast, ablated femurs from rats treated with PTH revealed a highly intense radiopacity ( Figure 1).…”
Section: Imaging Analysissupporting
confidence: 85%
See 3 more Smart Citations
“…When subjected to x-ray analysis, ablated femurs from rats treated with PBS revealed mildly enhanced radiopacity compared with control rats, similar to previous results in younger animals [2,3]. In contrast, ablated femurs from rats treated with PTH revealed a highly intense radiopacity ( Figure 1).…”
Section: Imaging Analysissupporting
confidence: 85%
“…This suggested that the new bone formed had, for the most part, been resorbed by osteoclasts. In contrast, the new bone formed in ablated femurs from rats treated with PTH was extremely abundant, to an extent that appeared similar to that reported previously in younger rats (Figure 4) [2,3]. Higher magnification analysis of that new bone revealed its lining by active osteoblasts, and the presence of small osteocytic lacunae, indicating that the new bone was being actively formed ( Figure 5).…”
Section: Histomorphometrysupporting
confidence: 84%
See 2 more Smart Citations
“…During wound healing macrophages phagocytose debris and apoptotic cells. PTH has robust anabolic actions during traumatic injuries associated with increased apoptosis such as bone marrow ablation (20). Hence, PTH could act in the marrow to recruit macrophages and promote the release of specialized pro-resolving mediators that facilitate efferocytosis.…”
Section: Resultsmentioning
confidence: 99%